PERLINDUNGAN HUKUM BAGI ANAK PELAKU TINDAK PIDANA KEJAHATAN SEKSUAL MELALUI DIVERSI DALAM SISTEM PERADILAN ANAK (JUVENILE JUSTICE SYSTEM) DI INDONESIA - Aras Firdaus; Alvi Syahrin; Marlina Marlina; Suhaidi Suhaidi (Universitas Sumatera Utara, 2016)
ABSTRACT Sexual crimes committed by children is not necessarily completely because of the desire of the children themselves. Children who commit violations of the law or committing criminal actions greatly influenced several other factors outside themselves like children Association, education, play and so on. Provide protection against children from the influence of the process of the formal criminal justice system, then the human thought has occurred or the legal and humanitarian experts to create formal rules of action issuing a child who commits a violation of the law or committing criminal acts from the criminal justice process by providing an alternative that is considered better for children. The issue raised in this research, is how form of legal protection for perpetrators of the criminal act of sexual crimes according to the provisions of laws and regulations, and how the role of law enforcement agencies in taking action against the perpetrators of the criminal act of sexual crime. Result the studies show that form of legal protection against the perpetrators of sexual violence can be seen inside and outside of the criminal code and code of criminal procedure. According to the provisions of the criminal code stated that the overthrow of a punishment to a child is the last effort, and concerns the punishment given to a child that is different to adults. Code of criminal procedure specifies the rights of the child who became the suspect or defendant upon the criminal deeds he had done. The role of law enforcement agencies in taking action against the perpetrators of the criminal act of sexual crimes began from the police institution is the institution of the first state to intervene against the child in conflict with the law. Arrests, anchoring, the investigation, and the investigation is the police authority to enforce the criminal justice system, which in the exercise of police authority given the task is diskresi where diskresi is the legal authority the authority in which the police has the right to continue or discontinue a matter. Based on this authority can divert police against a things of the child so that the child does not need to be confronted with the completion of the criminal court formally. Keywords: Sexual Violence, Children, Versioned